Alkylmethylimidazolium tricyanomethanide based supported ion gel membranes for CO2 separation. Issue 81 (3rd November 2017) - Hwang, Yongha; Cho, Eunhae; Jung, Jiyoon; Kang, Yong Soo; Won, Jongok
Abstract : Supported ion gel membranes with good mechanical stability for CO2 separation were prepared using triblock copolymers in an ionic liquid. Abstract : Supported ion gel membranes (SIGMs) with good mechanical stability for CO2 separation were prepared using triblock copolymers in an ionic liquid (IL). Ion gels were obtained by the addition of a small amount of poly(styrene- block -ethylene oxide- block -styrene) (SEOS) copolymer in the 1-alkyl-3-methylimidazolium tricyanomethanide family ([RMIm][TCM], with alkyl group R = ethyl (E), butyl (B) and hexyl (H)), and their properties were investigated. Mechanically stable SIGMs were prepared by self-assembly of [RMIm][TCM]/SEOS solution on the surface of the porous support, and their CO2 separation performances were measured. The ideal CO2 /CH4 separation factors were 9.7, 12.3 and 11.2 for the SIGMs containing [EMIm][TCM], [BMIm][TCM] and [HMIm][TCM], respectively. Morphological structure and complex formation, as determined by wide-angle X-ray diffraction analysis and theoretical calculations, respectively, were conducted to study the permselectivity. The SIGM of [BMIm][TCM] shows a higher selectivity than that of [EMIm][TCM], since the interaction with CO2 of [EMIm][TCM] is stronger than that of [BMIm][TCM] or [HMIm][TCM] and the large intermolecular distance of [EMIm][TCM] leads to the non-selective structure for CO2 transport.